In-Silico Investigation of PAI-1 Structural Changes in Active Forms of The Protein - Kaveh Haji-Allahverdipoor (Archives of Advances in Biosciences)
Introduction: Plasminogen activator inhibitor-1 (PAI-1) is a protein that plays an important role in regulating the fibrinolytic system, which is responsible for breaking down blood clots. Dysregulation of PAI-1 has been implicated in various diseases, including thrombosis, atherosclerosis, and cancer. Hence, expanding our knowledge of the PAI-1 structure is important for developing new therapies for these diseases. In this study, we aimed to compare the active form of Neovison and Human PAI-1 structures to rationalize pharmaceutical inhibitors in future studies. Materials and Methods: The Neovison PAI-1 protein model was generated using MODELLER, and the validity of the constructed model was confirmed through various validation servers. Subsequent analyses, including root mean square deviation (RMSD), root mean square fluctuation (RMSF), and solvent-accessible surface area (SASA), were performed over a 40 ns molecular dynamics (MD) simulation. Results: The data analysis of MD simulations and superimposed structures revealed that the stability of the Neovison PAI-1 protein is slightly higher than that of the Human PAI-1 protein; however, this difference is negligible. These findings were corroborated by the average RMSD, RMSF, and SASA plot values. Conclusion: These results suggest a new landscape for the design of inhibitors and enable a more accurate identification of the PAI-1 structure.